The Role of Emotions in Growing Cultural Awareness in Viral Marketing - Satrio, Danang (KnE Social Sciences, 2020)
Batik products are expected that Indonesian people will be able to dominate the Indonesian market. In realizing this, a marketing strategy that can use a cultural approach can be carried out. In applying the viral marketing model, emotions received by message recipients are expected to foster cultural awareness. Emotion is an important factor in the process of having cultural awareness (cultural awareness). The formation of cultural awareness in individuals is something that does not just happen but through various things and involves a variety of factors such as perception and emotions, awareness will be formed. The contribution of this research is to broaden the discussion about the role of emotions in the context of viral marketing especially for cultural products namely Batik and to identify the understanding of Indonesian cultural values. Keywords: Emotion, Viral Marketing, Cultural Awareness